Analysis of water quality in University Malaya rainwater harvesting system / Hasifa Hashim - Hasifa , Hashim (2019)
The aim of this study is to identify the condition of tanks located in the residential college and main building in University of Malaya and analyze water quality inside five chosen sample Rainwater Harvesting System (RWHS) tanks. The parameters analysed are compared with the National Water Quality Standards Malaysia (NWQS). The parameters that are measured in the study are temperature, pH, , total suspended solid (TSS), dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD) and ammoniacal nitrogen (NH3-N). The study showed that all parameters are between class I and III by National Water Quality Standards Malaysia (NWQS). The results showed that temperature, pH, TSS, DO, BOD, COD and NH3-N average values are 25.8°C-27.0°C, 5.82-7.02, 2.05-3.81mg/L, 5.4-7.3 mg/L, 1.34-1.43mg/L, 3.45-6.34 mg/L and 0.33-0.76 mg/L, respectively. The study highlighted good conditions and poor conditions of total 63 RWHS tanks in University Malaya and that there is a need to improve the condition of tanks. There are two poor conditions RWHS tanks, which are Kompleks Perdana Siswa UM (KPS) Tank A and Kinabalu Residential College (KK8) Tank A that unusable because of missing and broken pipes and not functioning in collecting rainwater. Therefore, prompt action needed for repair and maintenance work. 61 RWHS tanks are in good condition which it has good water flow and no broken parts. However, maintenance still in need to ensure good water quality and sustainable system. Control measures are introduced based on the interview method and observation from the field investigation as to ensure sustainable RWHS in University Malaya. This study also provides recommendations such as cleaning program and visual artwork to develop an awareness to use recycle water among University Malaya communities, hence the important of RWHS for sustainable environment.